Upaya Peningkatan Sikap Kerjasama Melalui Pendekatan Saintifik Model STAD - Praptiyani, Mulat; Sulistya Wardani, Naniek (Universitas Muhammadiyah Magelang, 2019)
This study aims to determine whether an increase in collaborative attitudes can be pursued through the STAD model scientific approach and how the steps of the STAD model scientific approach can improve the cooperative attitude of third grade students of Sidorejo Lor 03 Salatiga. The type of research used is classroom action research. Research procedures at least 2 cycles, each cycle carried out in 2 meetings. Eachccycle consists of planning, action and observation anddreflection. Data collection techniques use observation techniques with observation sheet instruments that are equipped with a measure of cooperation attitude measurement rubric. Theedata analysis technique used is the percentage technique to compare the attitude of cooperation between cycles. The results showed that there was an increase in the percentage of collaborative attitudes that were pursued through the STAD model scientific approach between cycles, namely 69% of all students with high collaborative attitude classifications inncycle 1 and increased to 100% of all students in cycle 2. Approach steps STAD scientific model that can improve the attitude of cooperation (1) convey the goals and motivations of students; (2) group formation @ 5 students; (3) presenting learning information about technological developments, (4) asking questions related to technological development material; (5) group discussion about information about technological developments; (6) presentation of main paragraph ideas and diversity of individual characteristics; (7) respond to the presentation results; (8) answer the quiz; (9) concludes; (10) acceptance of awards.